2012
DOI: 10.1186/1742-2094-9-202
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide attenuates spatial memory impairment and hippocampal neuroinflammation in beta-amyloid rat model of Alzheimer’s disease

Abstract: BackgroundEndogenously produced hydrogen sulfide (H2S) may have multiple functions in brain. An increasing number of studies have demonstrated its anti-inflammatory effects. In the present study, we investigated the effect of sodium hydrosulfide (NaHS, a H2S donor) on cognitive impairment and neuroinflammatory changes induced by injections of Amyloid-β1-40 (Aβ1-40), and explored possible mechanisms of action.MethodsWe injected Aβ1-40 into the hippocampus of rats to mimic rat model of Alzheimer’s disease (AD). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
102
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(107 citation statements)
references
References 53 publications
(57 reference statements)
4
102
0
1
Order By: Relevance
“…This is in line with previous report suggesting that NaHS could attenuate neuroinflammation in the hippocampus. 15 On the other hand, our data suggested that hepatic I/R could induce cognitive decline in rats and treatment with NaHS efficiently ameliorated such cognitive deficits. In sum, these results suggest NaHS alleviates hepatic I/R-induced cognitive impairment via inhibiting neuroinflammation, and NaHS has a significant anti-inflammatory effect in the central nervous system.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…This is in line with previous report suggesting that NaHS could attenuate neuroinflammation in the hippocampus. 15 On the other hand, our data suggested that hepatic I/R could induce cognitive decline in rats and treatment with NaHS efficiently ameliorated such cognitive deficits. In sum, these results suggest NaHS alleviates hepatic I/R-induced cognitive impairment via inhibiting neuroinflammation, and NaHS has a significant anti-inflammatory effect in the central nervous system.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, another study has demonstrated that NaHS could attenuate neuroinflammation and neuronal injury in brain. 15 Taken together, we speculated that NaHS protected against hepatic I/Rinduced cognitive deficits that are associated with reduced peripheral proinflammatory cytokines entering the brain and decreased local brain inflammation response and neuronal damages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…metabolism, suppress oxidative stress, have antiinflammatory effects, and shown to be neuroprotective in ischemia/reperfusion injury models of the central nervous system. 5,[27][28][29] We investigated whether inhalation of H 2 S was protective against CA and resuscitation-induced BBB disruption.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous findings because inflammation has been implicated as a critical mechanism responsible for the progressive nature of neurodegeneration (44,62), and there is an inverse link between an activated transsulfuration pathway and the immune response. In experimental models, H 2 S exerts antineuroinflammatory effects via inhibition of p38/Jun nuclear kinase and NF-κB signaling pathways (63), and the inhibition of CSE by PPG leads to increased inflammation (64). Furthermore, CSE has been shown to be a modulator of oxidative stress in mice (42).…”
Section: Discussionmentioning
confidence: 99%